2008
DOI: 10.1021/ja802472t
|View full text |Cite
|
Sign up to set email alerts
|

Planar Chiral Azobenzenophanes as Chiroptic Switches for Photon Mode Reversible Reflection Color Control in Induced Chiral Nematic Liquid Crystals

Abstract: In this report, for the first time, a planar chiral photoresponsive compound has been employed in commercially available nematic liquid crystals to achieve phototunable reflection colors. We designed an azobenzenophane compound having conformational restriction on the free rotation of naphthalene moiety to impose an element of planar chirality and the corresponding enantiomers were resolved by HPLC on chiral column. We have determined the absolute configuration by comparison of density functional theory (DFT) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
76
0
2

Year Published

2009
2009
2018
2018

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 154 publications
(79 citation statements)
references
References 70 publications
(43 reference statements)
1
76
0
2
Order By: Relevance
“…In 2008, Tamaoki et al reported a planar chiral dopant which was employed in commercially available nematic LCs to achieve phototunable reflection colors [113]. This compound was designed based on an azobenzenophane compound having conformational restriction on the free rotation of naphthalene moiety to impose an element of planar chirality.…”
Section: Single Chiral Photoresponsive Dopantmentioning
confidence: 99%
“…In 2008, Tamaoki et al reported a planar chiral dopant which was employed in commercially available nematic LCs to achieve phototunable reflection colors [113]. This compound was designed based on an azobenzenophane compound having conformational restriction on the free rotation of naphthalene moiety to impose an element of planar chirality.…”
Section: Single Chiral Photoresponsive Dopantmentioning
confidence: 99%
“…The melting points, clearing points, and the N*-SmA* phase transition temperatures are indeed all slightly higher than for the corresponding 2 -fluoro homologs; the SmA* phases all occur enantiotropically, indicating greater thermodynamic stability, unlike the preceding SmA* phases of the 2 -fluoro series (82)(83)(84)(85)(86)(87). This overall result may be partly due to the shielding of the 3-fluoro-substituent by the carboxylate linkage and the fact that the second fluoro-substituent effectively makes the liquid crystal core no broader (i.e., the second fluoro-substituent has little effect on the overall geometrical anisotropy of the molecule).…”
Section: Derivatives Of Chiral Alcoholsmentioning
confidence: 89%
“…This method is useful for measuring long pitch lengths by using very small amounts of material (5 × 10 −5 mg of dopant), and is a simpler alternative to complex chiral GC [72][73][74]. • Chiroptic Liquid Crystal Switches and Motors -here chiral photochemical dopants (chiral molecular motors) have been employed to manipulate the reflection wavelength of induced chiral nematic phases [75][76][77][78][79][80][81][82][83][84][85][86][87][88][89], as optical recording media, and to control the pitch and twist sense of material as a means of controlling viewing angle in LC displays [90].…”
Section: Applications Of Chiral Nematic Phasesmentioning
confidence: 99%
See 1 more Smart Citation
“…8, 12 Recently, we reported the first example of a photoresponsive planar chiral dopant in the form of a monocyclic azophane and successfully achieved a fast photon mode reversible full-range color control in induced cholesterics. 13 Here we report our success in 55 reversibly controlling the helical pitch length as well as the handedness of the induced helix by photochemical and thermal isomerizations of a planar chiral bicyclic azobenzenophane (1) in host nematic LCs. Target molecule was synthesized as pure trans isomer of the racemic compound E,E-1 and the structure was fully 85 characterized by NMR and X-ray crystallographic analysis.…”
mentioning
confidence: 97%